2012
DOI: 10.1186/1475-925x-11-77
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic micro sensor for the measurement of tendon forces

Abstract: A fiber optic sensor developed for the measurement of tendon forces was designed, numerically modeled, fabricated, and experimentally evaluated. The sensor incorporated fiber Bragg gratings and micro-fabricated stainless steel housings. A fiber Bragg grating is an optical device that is spectrally sensitive to axial strain. Stainless steel housings were designed to convert radial forces applied to the housing into axial forces that could be sensed by the fiber Bragg grating. The metal housings were fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…The understanding of these structures function and the interaction between them (Cleather and Bull, 2011;Collins and O'Connor, 1991;Pandy and Andriacchi, 2010) remains a challenge that could allow in the future assisting clinicians in term of diagnosis and treatments in case of orthopaedic or neurologic disorders. In vivo measurements of musculo-tendon, joint contact, ligament and bone forces exist (Behrmann et al, 2012;Bergmann et al, 2001;Bey and Derwin, 2012;Beynnon and Fleming, 1998;D'Lima et al, 2008;Lu et al, 1998), but the protocols are invasive and inappropriate for a daily clinical use (Fleming and Beynnon, 2004). Consequently, 3D musculoskeletal modeling of the lower limb has been proposed (Al Nazer et al, 2008;Anderson and Pandy, 2001;Cleather and Bull, 2011;Crowninshield and Brand, 1981;Fraysse et al, 2009;Glitsch and Baumann, 1997;Hu et al, 2013;Lenaerts et al, 2008;Moissenet et al, 2012a;Pierrynowski and Morrison, 1985;Seireg and Arvikar, 1975;Stansfield et al, 2003;Wehner et al, 2009) as an interesting alternative and several models have been developed (Arnold et al, 2010;Delp et al, 1990;Klein Horsman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of these structures function and the interaction between them (Cleather and Bull, 2011;Collins and O'Connor, 1991;Pandy and Andriacchi, 2010) remains a challenge that could allow in the future assisting clinicians in term of diagnosis and treatments in case of orthopaedic or neurologic disorders. In vivo measurements of musculo-tendon, joint contact, ligament and bone forces exist (Behrmann et al, 2012;Bergmann et al, 2001;Bey and Derwin, 2012;Beynnon and Fleming, 1998;D'Lima et al, 2008;Lu et al, 1998), but the protocols are invasive and inappropriate for a daily clinical use (Fleming and Beynnon, 2004). Consequently, 3D musculoskeletal modeling of the lower limb has been proposed (Al Nazer et al, 2008;Anderson and Pandy, 2001;Cleather and Bull, 2011;Crowninshield and Brand, 1981;Fraysse et al, 2009;Glitsch and Baumann, 1997;Hu et al, 2013;Lenaerts et al, 2008;Moissenet et al, 2012a;Pierrynowski and Morrison, 1985;Seireg and Arvikar, 1975;Stansfield et al, 2003;Wehner et al, 2009) as an interesting alternative and several models have been developed (Arnold et al, 2010;Delp et al, 1990;Klein Horsman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, most of FBG-based applications in this field have concerned the measurement of strain and force of ligaments and tendons from both animals and cadavers [26], [27]. Gratings have been embedded into microfabricated encapsulations made of shape memory alloys [27], stainless steel [28], or directly attached to the tissue [28]. The systems' response to applied loads and controlled strains have been monitored during static and dynamic conditions to find out the systems' metrological characteristics.…”
Section: ) Soft and Hard Tissuesmentioning
confidence: 99%
“…The systems' response to applied loads and controlled strains have been monitored during static and dynamic conditions to find out the systems' metrological characteristics. For instance, an FBG sensor housed into a micro-fabricated encapsulation made of shape memory alloy in [27] and of stainless steel in [28] was fabricated for strain and force sensing. Tests in static and dynamic conditions (e.g., at different loads and during loading-unloading cycles to simulate various postures and locomotion) were performed on a femoral cadaveric tendon and a ligament in [27], and on a bovine tendon in [28].…”
Section: ) Soft and Hard Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment results demonstrated that the sensor was found to be a sensitive and reliable method for acquiring minimally invasive measurements of soft tissue forces. 4 Guru Prasad et al described an ab initio design and development of an FBG sensor-based strain sensing plate for the measurement of plantar strain distribution in the human foot. 5 In this study, the traditional accelerometers were used to establish a reference platform to test the performance of the designed strain sensing plate based on FBG sensor.…”
Section: Introductionmentioning
confidence: 99%